Thou Shalt Forget Indigenous sovereignty, resistance and the production of cultural oblivion in Canada - Ross-Tremblay, Pierrot (HRC series, 2020)
What is 'cultural oblivion' and 'psychological colonialism', and how are they affecting the capacity of Indigenous Peoples in Canada to actively resist systematic and territorial oppression by the state? Following a decade-long research project, this new book by Pierrot Ross-Tremblay examines the production of oblivion among his own community, the Essipiunnuat [or, 'People of the Brook Shells River'] and the relationship between a colonial imperative to forget. The book illustrates how the 'cultural oblivion' of vulnerable minority communities is a critical human rights issue but also asks us to reflect upon both the role of the state and the local elite in creating and warping our perception and understanding of history.